2017
DOI: 10.3390/inorganics5020022
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Molecular Beryllium–Silicon Bonds

Abstract: We present the synthesis of two silyl beryllium halides HypSiBeX·(thf) (HypSi = Si(SiMe 3 ) 3 , X = Cl 2a, I 4a) and the molecular structure of 2a as determined by single crystal X-ray diffraction. Compounds 2a and 4a were characterized via multi-nuclear NMR spectroscopy ( 1 H, 9 Be, 13 C, 29 Si), and the bonding situation was further investigated using quantum chemical calculations (with the addition of further halides X = F 1b, Cl 2b, Br 3b, I 4b). The nature of the beryllium silicon bond in the context of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…With the additional help of quantum-chemical calculations it was demonstrated that the BeÀSi bond is mainly cova-lent in these compounds. [50] Monodentate phosphines proved to be rather good ligandsf or beryllium halides and the bisphosphine adduct [BeCl 2 (PMe 3 ) 2 ]( 50)w as obtained quantitatively by reactiono fB eCl 2 with PMe 3 in chlorinated or aromatic solvents. [51] Reaction of one equivalent of BeCl 2 with one equivalent of [Pd(PCy 3 ) 2 ]l eads to the formation of the relatedd inuclear species 51 through an unknown route.…”
Section: Beyond the Secondperiodmentioning
confidence: 99%
See 2 more Smart Citations
“…With the additional help of quantum-chemical calculations it was demonstrated that the BeÀSi bond is mainly cova-lent in these compounds. [50] Monodentate phosphines proved to be rather good ligandsf or beryllium halides and the bisphosphine adduct [BeCl 2 (PMe 3 ) 2 ]( 50)w as obtained quantitatively by reactiono fB eCl 2 with PMe 3 in chlorinated or aromatic solvents. [51] Reaction of one equivalent of BeCl 2 with one equivalent of [Pd(PCy 3 ) 2 ]l eads to the formation of the relatedd inuclear species 51 through an unknown route.…”
Section: Beyond the Secondperiodmentioning
confidence: 99%
“…Various beryllium compounds with Lewis bases. [21,24,50,[52][53][54][55] Scheme6.Di(n-butyl)beryllium synthesis utilizing PMe 3 as solubilizer. [51] Chem.…”
Section: Beyond the Secondperiodmentioning
confidence: 99%
See 1 more Smart Citation
“…The beryllium atom is coordinated pseudotetrahedrally by two SMe 2 and two phenyl ligands. The S−Be−S, C−Be−C and C− Be−S angles are 99.60 (10), 120.20 (16), and 106.92(5)/ 110.65(5)°, respectively. These are comparable to the corresponding angles in [(SMe 2 ) 2 BeBr 2 ] (S−Be−S: 96.6(2)°, Br−Be−Br: 117.6(2)°, S−Be−Br: 106.92(3)−113.47(4)°), 41 while the S−Be−S angles in [(NH 3 )(Py)Be(SPh) 2 ] are significantly larger (124.6(2)−125.2(2)°).…”
Section: ■ Introductionmentioning
confidence: 99%
“…In contrast to the ubiquity of organomagnesium reagents, organoberyllium chemistry is relatively unexplored due, at least in part, to the perceived toxicity of this element. Indeed, although organoberyllium complexes were prepared as early as the 1920s, the field has subsequently been relatively devoid of methodical, fundamental beryllium research. Recently, there has been renewed interest in the organometallic chemistry of beryllium, driven by a desire to understand the biotoxicity mechanisms of this element and exploit its unique electronic properties for chemical transformations. Within the past five years, the first compounds containing formally zero- and monovalent beryllium centers, in addition to the first BeC and BeN bonds have all been reported. …”
Section: Introductionmentioning
confidence: 99%